Contemporary Issues in African Sciences and Science Education
XII, 238 p.
Keywords: In this careful articulation of science, the editors provide an intellectual marriage of Indigenous science and science education in the African context as a way of revising schooling and education. They define science broadly to include both the science of the natural/physical/biological and the ‘science of the social’. It is noted that the current policy direction of African education continues to be a subject of intense intellectual discussion. Science education is very much at the heart of much current debates about reforming African schooling. Among the ways to counter-vision contemporary African education this book points to how we promote Indigenous science education to improve upon African science and technology development in general. The book also notes a long-standing push to re-examine local cultural resource knowings in order to appreciate and understand the nature, content and context of Indigenous knowledge science as a starting foundation for promoting African science and technology studies in general. It is argued that these interests and concerns are not mutually exclusive of each other but as a matter of fact interwoven and interdependent. The breadth of coverage of the collection reflect papers in science, Indigeneity, identity and knowledge production and the possibilities of creating a truly African-centred education. It is argued that such extensive coverage will engage and excite readers on the path of what has been termed ‘African educational recovery’. While the book is careful in avoiding stale debates about the ‘Eurocentricity of Western scientific knowledge’ and the positing of ‘Eurocentric science’ as the only science worthy of engagement, it nonetheless caution against constructing a binary between Indigenous/local science and knowledges and Western ‘scientific’ knowledge. After all, Western scientific knowledge is itself a form of local knowledge, born out of a particular social and historical context.Engaging science in a more global context will bring to the fore critical questions of how we create spaces for the study of Indigenous science knowledge in our schools. How is Indigenous science to be read, understood and theorized? And, how do educators gather/collect and interpret Indigenous science knowledges for the purposes of teaching young learners. These are critical questions for contemporary African education?